Pengembangan E-LKPD Berbasis Poblem Based Learning (PBL) Terintegrasi Berpikir Kritis Pada Materi Sistem Ekskresi Manusia Kelas XI SMA - Gultom, Putri Rohani; Wan Syafi’i; Darmadi (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to develop an Electronic Student Worksheet (E-LKPD) based on Problem-Based Learning (PBL) integrated with critical thinking skills on the topic of the human excretory system for Grade XI senior high school students. The research employed a Research and Development (R&D) approach by adapting the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). This study was conducted up to the development stage. The trial subjects included two expert validators, 10 biology education students, two biology teachers, and 30 Grade XI students from SMAN 2 Pekanbaru. The instruments used consisted of a validation sheet, student response questionnaire (students and prospective teachers), and teacher response questionnaire. The validation results showed that the E-LKPD was categorized as